1961
DOI: 10.1001/archpedi.1961.02080010182005
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Observations During Birth of the Lamb

Abstract: In the process of birth, very complex circulatory changes occur during the transition from fetal to neonatal states. Because of the rapidity of these important changes and the dangers involved in their study, observations of the human infant have been limited. Studies of some of the physiologic changes that occur at birth of the newborn lamb have been performed by Barcroft,1 Barron,2 Dawes,3-11 Born,12-15 and others.16-18 The findings of these workers have provided insight into the circulatory changes at birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1963
1963
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…This is in agreriiient with earlier reports of the stimulating effect on breathing of hypoxia I ci-05~. Killich and Hugget 1954) and of umbilical cord clamping (Harned et al 1961 , . The lowering of the heart rate observed in newborn rats kept in an atmosphere of reducr-bd oxygen is similar to observations on lambs in utero (Assali, Holm and Sehgal 1962 I . Lowering of the heart rate in newborn rats also follows a decrease in the en\-ircmniental teniprrature (Fairfield 1948). A decrease in the temperature from 37 C: to 30' C reduced the heart rate from 310 to 210 cycles per minute, without an) dfect on the ductal closure (Hornblad and Larsson 196713).…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreriiient with earlier reports of the stimulating effect on breathing of hypoxia I ci-05~. Killich and Hugget 1954) and of umbilical cord clamping (Harned et al 1961 , . The lowering of the heart rate observed in newborn rats kept in an atmosphere of reducr-bd oxygen is similar to observations on lambs in utero (Assali, Holm and Sehgal 1962 I . Lowering of the heart rate in newborn rats also follows a decrease in the en\-ircmniental teniprrature (Fairfield 1948). A decrease in the temperature from 37 C: to 30' C reduced the heart rate from 310 to 210 cycles per minute, without an) dfect on the ductal closure (Hornblad and Larsson 196713).…”
Section: Discussionsupporting
confidence: 90%
“…However, as FBM are restricted to levels of fetal activity, they are discontinuous, occurring <50% of the time. Further, although most FBM generate transpulmonary pressures of <20 cm H 2 O, fetuses commonly can make large inspiratory efforts (>30 cm H 2 O) [9,10], demonstrating that they are capable of generating transpulmonary pressures needed to aerate the lungs after birth [7]. The mechanisms controlling the switch to continuous breathing after birth are currently unknown.…”
Section: Pulmonary Transitionmentioning
confidence: 99%
“…Data on this matter are scarce, although animal studies have shown that cooling lambs at birth elicits normal quiet breathing, but no large initial gasps [8]. In contrast, painful stimuli elicit gasps in unanesthetized lambs with an intact umbilical cord, but not sustained respiratory movements [9]. …”
Section: Pulmonary Transitionmentioning
confidence: 99%